PERANAN LETDA ABDUL MURAD SAIDUN DALAM MEMPERTAHANKAN KEMERDEKAAN INDONESIA DI SELATPANJANG (1945-1950) - Juheri Septiawan; Kamaruddin '; Bunari ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Letda Abdul Murad Saidun is a member of the military in the physical revolution Selatpanjang in the years 1945-1950. During the Japanese occupation, the Letda Abdul Murad Saidun joined the Japanese military organization heiho. Post-reading the text of the proclamation of Ir. Soekarno and Moh. Hatta, Letda Abdul Murad Saidun resumed his military career by joining the People's Security Agency (BKR), which is a progression to the Indonesian National Army (TNI) as the base defense in maintaining state sovereignty. After Letda Abdul Murad Saidun participate BKR in Selatpanjang, he is believed to be the deputy military commander of Company II Selatpanjang by Lieutenant. Col. Hasan Basri who is head of Regiment IV Riau. The purpose of this research is to know the life story of LetdaAbdul Murad Saidun, to find out how the role and fights Letda Abdul Murad Saidun uphold the independence of Indonesia in Selatpanjang, to determine the end of the match Letda Abdul Murad Saidun. The method used in this research is the method of historical and descriptive method in which data were collected through interviews and analyzed in its own language. The research location is in Selatpanjang Meranti Islands regency in Riau province. When the study started from the exam proposal for the final exam. Data collection techniques used were interview techniques, technical documentation and technical literature. From study said that Letda Abdul Murad Saidun is one of the military leaders in Selatpanjang. Based on these results, we can conclude that LietdaAbdul Murad Saidun has a big role in fighting to preserve the independence of Indonesia, especially in Selatpanjang.Keywords: Position, Maintain, Independence